Construction and immunogenicity of a trypsin-independent porcine epidemic diarrhea virus variant - Li, Mingxiang; Zhang, Yiye; Fang, Yuxin; Xiao, Shaobo; Fang, Puxian; Fang, Liurong (Frontiers in Immunology, 2023)
Porcine epidemic diarrhea virus (PEDV) is a re-emerging enteropathogenic coronavirus that causes high mortality in neonatal piglets. The addition of trypsin plays a crucial role in the propagation of PEDV, but also increases the complexity of vaccine production and increases its cost. Previous studies have suggested that the S2' site and Y976/977 of the PEDV spike (S) protein might be the determinants of PEDV trypsin independence. In this study, to achieve a recombinant trypsin-independent PEDV strain, we used trypsin-dependent genotype 2 (G2) PEDV variant AJ1102 to generate three recombinant PEDVs with mutations in S (S2' site R894G and/or Y976H). The three recombinant PEDVs were still trypsin dependent, suggesting that the S2' site R894 and Y976 of AJ1102 S are not key sites for PEDV trypsin dependence. Therefore, we used AJ1102 and the classical trypsin-independent genotype 1 (G1) PEDV strain JS2008 to generate a recombinant PEDV carrying a chimeric S protein, and successfully obtained trypsin-independent PEDV strain rAJ1102-S2JS2008, in which the S2 (amino acids 894–1386) domain was replaced with the corresponding JS2008 sequence. Importantly, immunization with rAJ1102-S2'JS2008 induced neutralizing antibodies against both AJ1102 and JS2008. Collectively, these results suggest that rAJ1102-S2'JS2008 is a novel vaccine candidate with significant advantages, including no trypsin requirement for viral propagation to high titers and the potential provision of protection for pigs against G1 and G2 PEDV infections.